Mechanism and application of thiol–disulfide redox biosensors with a fluorescence-lifetime readout - Paul C. Rosen; Andrew Glaser; Juan R. Martínez-François; Daniel C. Lim; Daniel J. Brooks; Panhui Fu; Erica Kim; Dorothee Kern; Gary Yellen (Proceedings of the National Academy of Sciences, 2025)
Genetically encoded biosensors with changes in fluorescence lifetime (as opposed to fluorescence intensity) can quantify small molecules in complex contexts, even in vivo. However, lifetime-readout sensors are poorly understood at a molecular level, complicating their development. Although there are many sensors that have fluorescence-intensity changes, there are currently only a few with fluorescence-lifetime changes. Here, we optimized two biosensors for thiol–disulfide redox (RoTq-Off and RoTq-On) with opposite changes in fluorescence lifetime in response to oxidation. Using biophysical approaches, we showed that the high-lifetime states of these sensors lock the chromophore more firmly in place than their low-lifetime states do. Two-photon fluorescence lifetime imaging of RoTq-On fused to a glutaredoxin (Grx1) enabled robust, straightforward monitoring of cytosolic glutathione redox state in acute mouse brain slices. The motional mechanism described here is probably common and may inform the design of other lifetime-readout sensors; the Grx1-RoTq-On fusion sensor will be useful for studying glutathione redox in physiology.